BS EN 63115-1 AMD1. Secondary cells and batteries containing alkaline or other non-acid electrolytes. Sealed nickel-metal hydride cells and batteries for use in industrial applications. Part 1. Performance (24th January 2022) - British Standards Institution
No abstract available